Communication Strategies of the Madrasah Principal in Improving the Quality of Educational Institutions: A Case Study at MTs Al-Hikmah Purwoasri, Kediri - Aina Ainaul Mardliyah; Ahmad Tanzeh; Binti Maunah (World Journal of Islamic Learning and Teaching, 2026)
The dynamics of the development of Madrasah Tsanawiyah (MTs) Al Hikmah cannot be separated from the role of the principal’s communication. Analogous to the human body, communication functions as blood that must flow to all parts. This constitutes one of the foundations for quality development. The communication strategy of the principal of MTs Al Hikmah in quality development exhibits distinctive characteristics. The principal is able to establish highly effective communication despite not having an educational background in communication studies. The principal employs prophetic-based communication strategy to enhance institutional quality. This study is qualitative research employing a phenomenological approach. Data were collected through interviews with the principal, foundation caretakers or administrators, teachers, parents or students, and stakeholders. In addition, interview data were systematically dialogued with documents and observations. After data collection, the data were analyzed using prophetic and quality-based approaches. The analytical process involved data condensation and triangulation to ensure the scientific accountability of the findings. The communication implemented operates effectively according to its roles as persuasive, informative, collective-regulative, and integrative, with a linear pattern through channels of direction, instruction, and task assignment aligned with institutional objectives. (b) The direction of the communication strategy is predominantly top-down rather than bottom-up within formal school contexts, guided by ethics of liberation, humanization, and decentralization. Diagonal communication is conducted with several informants, such as vice principals for curriculum, student affairs, and facilities and infrastructure, through various communication platforms. Interpersonal communication is also well established, with a strong emphasis on motivating subordinates from multiple perspectives.